(untitled) (In situ, 2024)
Within the preparatory works for the development of the part of the coast east of the Baotić marina in Seget Donji, the University of Zadar, the Department of Archeology and the Stratum d. o. o. company carried out archaeological rescue excavations with the aim of determining the presence of possible archaeological remains in the mentioned area. Archaeological field research revealed traces of filling the entire area with earth and amorphous stones from the post-medieval to recent periods, and underwater research revealed traces of the coastal line from the Roman period, as well as the remains of an ancient quay built from the 1st to the 3rd century. In the centuries that followed, until the present day, the rise of the sea level flooded the ancient coast, and today it is located about 30 meters away from the current coast.